China’s International Strategy and How to Pursue It - Chairul Aftah (Institute of International Studies, 2014)
China is a major actor in the Asia Pacific region and global because of its economy, politic, military, social and cultural capabilities. In world history, this position has been built through several stages. In the Post-World War II, China was considered dangerous despite its inability to show diplomatic influence in international relations, especially with the United States and its allies. It was only after 1980, after Deng Xiaoping came to power, China began to increase their influence through a variety of domestic and international policies. As a result, China’s existence has been increasingly recognized in various fields. Domestically, China considers that the increase of its multisectoral capability as an effort to put China on an equal footing with other actors that have better capabilities. In contrast, for the other states, the increase of China’s ability has been perceived as a threat because it raised China’s bargaining power. Thus, it is crucial for China to convince others that its progress is not a threat. In improving its capabilities, China formulated an international strategy in both regional and international level. Therefore, China sought to implement these strategies by improving its relationship with other actors.